Cryopreserved Umbilical Cord Extract Restores the Skin Structure in Ovariectomized Rats - Falko, Oksana; Shevchenko, Nadiia; Volina, Viktoria; Terekhova, Olena; Prokopyuk, Olga; Kaverinska, Anna; Karpenko, Volodymyr; Prokopyuk, Volodymyr (Problems of Cryobiology and Cryomedicine, 2024)
The research covers the specific effect of human umbilical cord cryoextract and the culture medium of its mesenchymal stromal cells in comparison with synthetic hyaluronic acid on the skin regeneration in female rats with simulated aging. The specified substances were administered intradermally to ovariectomized animals. The injection of human umbilical cord cryoextract into animals with a model of skin aging was established to restore the skin structure already 2 weeks after the injections. Thickening of the epidermis and dermis, phenomenon of cell proliferation, and an increased number of collagen fibers as well as blood vessels were observed. Four weeks after the last injection, the skin condition was normalized to the level of intact animals. Administration of the culture medium of mesenchymal stromal cells of the umbilical cord also led to an increased number of collagen fibers, cell proliferation, contouring of skin layers, but had a less pronounced effect compared to the injections of cryoextract on the indices of the dermis and epidermis thickness. Injections of synthetic hyaluronic acid led to "rejuvenation" of the upper layers of skin and had a less pronounced manifestation compared to the effect of human umbilical cord derivatives. Probl Cryobiol Cryomed 2024; 34(1):033–044